Capitéis romanos da Igreja de Santa Maria de Alcáçova em Santarém - Fernandes, Lídia (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
Five capitals from the Church of Stª. Maria in Santarém are presented, considering their chronology as well as its manufacturing techniques and its stylistics aspects. Therefore, some more embraced aspects, regarding their integration according to the usual decorative forms within the empire, are taken into consideration, a long with their architectural framing and the manufactures that produced them.